RESISTENSI PUBLIK KOREA SELATAN TERHADAP PESAN FEMINISME DALAM FILM BARBIE (2023) - Farida Zayanti; Raden Maisa Yudono (LPPM Universitas Negeri Surabaya, 2025)
This study aims to analyze how public resistance in South Korea toward the feminist messages in the film Barbie (2023) is formed and interpreted. The film was selected as the subject of analysis due to its articulation of feminist ideas through narratives of critique against patriarchy, women's empowerment, and gender equality. However, these messages were not universally accepted. South Korea, a society still heavily influenced by patriarchal structures and Confucian values, demonstrates a complex response to the film’s feminist representation. This research employs a qualitative approach through document analysis and literature review. The data sources include the film’s content, academic literature, public responses on South Korean online platforms, and related media coverage. The findings indicate that public resistance in South Korea is manifested in institutional, symbolic, and performative forms. These range from the censorship of promotional materials and vandalism of posters to online rating sabotage and performative actions such as walking out of theaters. These expressions reflect a rejection of feminist narratives perceived as threatening to the existing social order. Such resistance does not merely indicate a mismatch of values but also reveals a broader social unease in the face of shifting gender roles. Using the frameworks of postcolonial feminism and backlash theory, this study highlights how the clash between global feminist values and local identity becomes a critical site for understanding the dynamics of feminist reception in the international context. Keywords: Barbie Film, Feminism, Resistance, South Korea